Preferred step frequency during downhill running may be determined by muscle activity - Sheehan, R. C.; Gottschall, J. S. (Journal of Electromyography and Kinesiology, 2013)
It is well established that metabolic cost is minimized at an individual`s running preferred step frequency (PSF). It has been proposed that the metabolic minimum at PSF is due to a tradeoff between mechanical factors, however, this ignores muscle activity, the primary consumer of energy. Thus, we hypothesized that during downhill running, total muscle activity would be greater with deviations from PSF. Specifically, we predicted that slow step frequencies would have greater stance activity while fast step frequencies would have greater swing activity. We collected metabolic cost and leg muscle activity data while 10 healthy young adults ran at 3.0 m/s for 5 min at level and downhill at PSF and ±15% PSF. In support of our hypothesis, there was a significant main effect for step frequency for both metabolic cost and total muscle activity. In addition, there was greater muscle activity in the stance phase during the slower step frequency while muscle activity was greater in the swing phase during the fast step frequency. This suggests that PSF is partially determined by the tradeoff between the greater cost of muscle activity in the swing phase and lower cost in the stance phase with faster step frequency.